Part II: presentation, diagnosis, classification, treatment, and prevention of stress fractures in female athletes. Issue 1 (2nd January 2020) - Abbott, Alexandra; Bird, Mackenzie; Brown, Symone M.; Wild, Emily; Stewart, Greg; Mulcahey, Mary K.
ABSTRACT: Objectives : Stress fractures (SFx) occur as the result of repetitive loads over short periods of time, which leads to micro-damage of the bone through cortical resorption, ultimately leading to fracture. They are a common injury in female athletes and often cause significant morbidity. The goal of this study is to review the presentation, diagnosis, classification, treatment, and prevention of SFx in female athletes. Results : A thorough history, physical exam, and appropriate imaging can facilitate early diagnosis of stress fracture (SFx) and faster resolution of symptoms with more conservative management. The female athlete triad is an especially important factor that contributes to the increased risk of SFx in females. The continuum of stress injuries ranges from mild microfailure to complete fracture, which has resulted in the development of newer grading schemas through MRI and radiographic findings. Stress fractures are also classified as low- or high-risk according to anatomic location, as blood supply and applied forces at different locations affect the likelihood of fracture propagation, displacement, delayed union, or non-union. Conclusions : The ability to screen for at-risk athletes is paramount in preventing SFx. Recognition and prompt treatment of the female athlete triad requires a multidisciplinary approach in order to restore energy balance, correct menstrual irregularities, and improve bone health. This review provides a basis for understanding how to identify and treat stress fractures, which may allow treating physicians to diagnose this condition earlier and minimize any associated morbidity.